Lattice Boltzmann Simulations of Two Linear Microswimmers Using the Immersed Boundary Method (Communications in Computational Physics, 2023)
The performance of a single or the collection of microswimmers stronglydepends on the hydrodynamic coupling among their constituents and themselves. Wepresent a numerical study for a single and a pair of microswimmers based on latticeBoltzmann method (LBM) simulations. Our numerical algorithm consists of two separable parts. Lagrange polynomials provide a discretization of the microswimmers andthe lattice Boltzmann method captures the dynamics of the surrounding fluid. Thetwo components couple via an immersed boundary method. We present data for asingle swimmer system and our data also show the onset of collective effects and, inparticular, an overall velocity increment of clusters of swimmers.